Therapeutic effects of mesenchymal stem cells and their derivatives in common skin inflammatory diseases: Atopic dermatitis and psoriasis - Yang, Jie; Xiao, Minglu; Ma, Kui; Li, Hongyu; Ran, Mingzi; Yang, Shuxu; Yang, Yuguang; Fu, Xiaobing; Yang, Siming (Frontiers in Immunology, 2023)
Chronic skin inflammatory diseases including atopic dermatitis (AD) and psoriasis have been considered uncontrolled inflammatory responses, which have usually troubled patients around the world. Moreover, the recent method to treat AD and psoriasis has been based on the inhibition, not regulation, of the abnormal inflammatory response, which can induce a number of side effects and drug resistance in long-term treatment. Mesenchymal stem/stromal cells (MSCs) and their derivatives have been widely used in immune diseases based on their regeneration, differentiation, and immunomodulation with few adverse effects, which makes MSCs a promising treatment for chronic skin inflammatory diseases. As a result, in this review, we aim to systematically discuss the therapeutic effects of various resources of MSCs, the application of pre-conditioning MSCs and engineering extracellular vesicles (EVs) in AD and psoriasis, and the clinical evaluation of the administration of MSCs and their derivatives, which can provide a comprehensive vision for the application of MSCs and their derivatives in future research and clinical treatment.